Penambahan Tepung Wortel (Daucus carota) dalam Pakan untuk Peningkatan Warna Ikan Mas Koki (Carassius auratus) - Anhar Diansyah; Mohamad Amin; Yulisman Yulisman (Jurnal Akuakultur Rawa Indonesia, 2019)
The goldfish is a ornamental fish that it has color of variations from red, yellow, white, orange, black and silver . The study aims to determine the effect from the addition carrot flour the feed to improve the color of the goldfish. This research was conducted on October - November 2018 at Laboraturium Kolam Percobaan, Aquaculture Study Program, Faculty of Agriculture Sriwijaya University. Design the study used a Completely Randomized Design (CRD) consist four treatments with three replications namely (T0) without carrot flour, (T1) 5% carrot flour in feed, (T2) 10% carrot flour in feed, (T3) 15% carrot flour in the feed. Parameters observed improving of goldfish, weight of fish, feed consumption, survival rate and water quality (temperature, pH and DO). The result showed of the study obtained a total comparison of the differences in color of goldfish was 8.15 (T0), 24.23 (T1), 22.92 (T2) and 18.75  (T3). Weight was T0 (0,87 cm - 0,85 g), T1 (0,99 cm - 1.04 g), T2 (0,89 cm - 0,63) and T3 (0,99 cm - 0,54 g). Feed consumption was T0 (9,25), T1 (9,94), T2 (12,00) and T3 (11,77). Survival rate was T0 (93,33%), T1 (100,00%), T2 (100,00%) and T3 (100,00%).  Water  quality during maintenance were temperature 25.0 – 35.8 0C, pH 6.5 – 8.9, DO 4.09 – 6.30 mg/L.